Evaluation of Socioeconomic Determinants of Quality of Life among Healthcare Providers - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Background: In literature, fewer studies are evident that quality of life (QoL) among healthcare providers (HCPs) is a paramount concern, especially to have optimum and best patient care. If the QoL of the HCPs is not up to the satisfactory level, it will have a direct effect on QoL of their patients. Objective: This study aimed to determine socioeconomic determinants of QoL among HCPs in Malaysia. Materials and Methods: A cross-sectional study was conducted using among HCPs using World Health Organization QoL-BREF using a convenience sampling method. The socioeconomic determinants of QoL among HCPs were determined using descriptive and inferential statistics. Data were entered and analyzed using Statistical Package for the Social Sciences ver. 24.0. Results: Out of total (n = 310) studied HCPs, more females (n = 188, 60.6%), than males (n = 122, 39.4%) participated in this study. According to the study findings, in the psychological domain, marital status, in social domain marital status and job nature, and in environmental domain experience were observed as pure socioeconomic determinants that showed statistically significant values (P < 0.05). Conclusion: In Malaysia, overall, the HCPs had better QoL and had good access to excellent healthcare services, self-confidence, and social life.